Effects of Rosmarinus officinalis on the survivability of random-patterned skin flaps: An experimental study - Ince, Bilsev; Yildirim, Alpagan Mustafa; Okur, Mehmet Ihsan; Dadaci, Mehmet; Yoruk, Ebru (Taylor & Francis Ltd, 2015)
Improving survival of skin flaps used in soft-tissue reconstruction is clinically an important goal, and several systemic and local agents have been used for this purpose. However, a substance that prevents the flap necrosis has not yet been defined. This study aimed to investigate whether a Rosmarinus officinalis extract could improve the skin flap survival. In this study, 21 Wistar albino rats were divided into three groups. Rectangular 8 x 2 cm random-pattern flaps were elevated from the back of the rats. Group I was considered the control group. In Group II, a 0.5-cc of Rosmarinus officinalis oil was applied with an ear bud to the flap area 30 minutes before the flap elevation. After suturing the flaps to their location, the oil was administered twice a day for a week. In Group III, 0.5 cc of the oil was applied twice a day to the area that was elevated for a week until surgery. At the end of the week, the flaps were sutured to their location, and wiped postoperatively twice a day for a week with the oil. Mean percentage of these areas was found to be 29.81%, 58.99%, and 67.68% in Group I, Group II, and Group III, respectively. The mean percentage of the flap survival areas and vessel diameters were significantly greater in the Groups II and III than in the control group (p < 0.05). The results revealed that the topical use of the Rosmarinus officinalis extract can increase the flap survivability.
Keywords: Tissue defect; repair; rosmarinus officinalis; flap survivability